2022
DOI: 10.1039/d2dt00788f
|View full text |Cite
|
Sign up to set email alerts
|

A bioinspired redox-modulating copper(ii)–macrocyclic complex bearing non-steroidal anti-inflammatory drugs with anti-cancer stem cell activity

Abstract: Copper(II) coordination compounds have been investigated for their anticancer properties for decades, however, none have reached advanced human clinical trials. The poor translation of copper(II) complexes from in vitro studies...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Furthermore 1 was significantly more potent towards breast CSCs than previously reported anti-breast CSC copper( ii ) complexes: 3-fold more potent than copper( ii ) complexes containing phenanthroline-based and indomethacin ligands, 43 52-fold more toxic than copper( ii ) complexes containing Schiff base and naproxen ligands, 46 and 18-fold more toxic than copper( ii ) complexes containing dithiacyclam and diclofenac ligands. 47…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore 1 was significantly more potent towards breast CSCs than previously reported anti-breast CSC copper( ii ) complexes: 3-fold more potent than copper( ii ) complexes containing phenanthroline-based and indomethacin ligands, 43 52-fold more toxic than copper( ii ) complexes containing Schiff base and naproxen ligands, 46 and 18-fold more toxic than copper( ii ) complexes containing dithiacyclam and diclofenac ligands. 47…”
Section: Resultsmentioning
confidence: 99%
“…Dalton Transactions up to 24 hours, indicating the stable nature of all the complexes in DMSO. 5,21 In vitro DNA binding studies DNA is the primary therapeutic target for most of the anticancer drugs in clinical use; therefore, it becomes imperative to study the interactions of potential drug candidates with their therapeutic target biomolecules. DNA exists as a supercoiled double helix, comprising complementary nucleobases, G-C and A-T sequences, which are stabilized by hydrogen bonds and π-π stacking interactions, giving rise to many amenable binding sites.…”
Section: Papermentioning
confidence: 99%
“…[1][2][3][4] Repurposing drugs for the treatment of other chronic diseases including cancer is a recent technological niche to utilize the resources of 'active' pharmaceuticals for remedies with improved therapeutic responses and better pharmacokinetic profiles than that of existing drugs. 5,6 Previous reports in the literature have revealed the strong relevance of histamines to the regulation of several tumors such as cervical, ovarian, uterine, colorectal cancer and melanoma by promoting or inhibiting their growth. 7 For example, Marja Jaattela et al have reported the use of cationic antihistamines for the treatment of non-small-cell lung cancer (NSCLC) 8 (which is the leading cause of cancer death globally), which provides a sound rationale for the use of histamine compounds for the treatment of cancers.…”
mentioning
confidence: 99%
“…the Cu( i ) and Cu( ii ) complexes of the trans -dithiacyclam derivative have been suggested as analogs of blue copper proteins and copper monooxygenases, 17–19 and its Cu( ii ) complex with two molecules of diclofenac, a nonsteroidal anti-inflammatory drug (NSAID) at the axial positions, has been used to generate reactive oxygen species (ROS) for killing breast cancer cells and highly resistant breast cancer stem cells. 20…”
Section: Introductionmentioning
confidence: 99%
“…the Cu(I) and Cu(II) complexes of the trans-dithiacyclam derivative have been suggested as analogs of blue copper proteins and copper monooxygenases, [17][18][19] and its Cu(II) complex with two molecules of diclofenac, a nonsteroidal anti-inflammatory drug (NSAID) at the axial positions, has been used to generate reactive oxygen species (ROS) for killing breast cancer cells and highly resistant breast cancer stem cells. 20 In the last couple of years, we have systematically investigated the coordination chemistry and electrochemical properties of Cu(II) cyclen derivatives substituted with one sulfur or one and more oxygen donors. 6,7 To find out if exchanging nitrogen donors in Cu(II) cyclen [Cu( [12]aneN 4 )] (CuL 1 ) with several sulfur atoms also had an effect on nuclease activity, CuL 2 -CuL 5 were prepared and their DNA cleavage activity was compared to that of CuL 1 .…”
Section: Introductionmentioning
confidence: 99%